Pola Asuh Orangtua Dan Kurangnya Gizi Anak Penyebab Stunting Di Desa Karangduwur, Kalikajar, Wonosobo - Christina Christina; Gunawan Gunawan; Renofiar Sultanea; Dini Lestari; Ulfa Azizah; Haniifah Haniifah; Tatik Yulatifah; Rian Fatimah; Ahmad Muzaki; Misbahul Munir; M.Maftuh Farhan (Jurnal Pengabdian Masyarakat Madani, 2022)
Stunting is a problem that still haunts children in Indonesia. To produce healthy and intelligent children in Indonesia, the most important first step to take is the fulfilment of nutrition in children from an early age. This research is an observational study, with a cross-sectional design using a qualitative approach in Karangduwur village, Kalikajar district, Wonosobo regency. Data are collected by means of interview with parents whose children show signs of stunting. The result reveals that three factors contribute in parenting style. They are related to feeding system, social economic, and education. Proper education on stunting changes people’s mindset and parenting to eliminate future cases.